Pengaruh Penerapan Media Interaktif Berbasis Multimedia Untuk Pembelajaran Bahasa Inggris Di MTs. NW Ketangga Menggunakan Algoritma Naïve Bayes - Yahya Yahya; Amri Muliawan Nur (Infotek: Jurnal Informatika dan Teknologi, 2022)
The digital era is an era where almost all daily activities are facilitated by the presence of technology. Our entry into the digital era is a sign that old ways will be abandoned which are then replaced with new technologies and ways that are more practical and modern. These changes have changed the perspective and practice of learning in the world of education today. In order to carry out an effective and efficient education, the existence of learning media is very urgent, especially in the future. Moreover, since the COVID-19 virus has paralyzed almost all activities and has had a very large influence on teaching and learning activities at schools. The use of multimedia-based learning media in English lessons is expected to increase enthusiasm and interaction between teachers and students. Given that English has become the language most often used in various countries, both in social life and in the work environment. Learning media will be equipped with animations that will attract the attention of students, as well as with explanations that will make students understand the lesson faster. In addition, there are other additional elements in the form of audio, to make it easier for students to understand the pronunciation or pronunciation of words or sentences in the subject matter. The application of this interactive media will be used as material to obtain data about the effect of interactive media in increasing student understanding. The data collection results were processed using RapidMiner 5.0 Tools and the Naïve Bayes Algorithm. The results of data processing show an accuracy value of 90.96%, which means that the application of interactive media to English subjects in MTs. NW Ketangga is very influential in increasing students' interest and ability in understanding the material presented